PROPOSED STRATEGY FORMULATION FOR PT. DKI (The Indonesian Journal of Business Administration, 2021)
Due to Indonesia’s inability to achieve self-sufficiency in soybeans production, we are increasingly relying on US soybeans imports to fulfil the national protein demand for human consumption. The diverse usage ranges from traditional tofu, tempeh, soy sauce, snacks and drinks production. Henceforth, the oilseed is also the primary source of affordable protein and has contributed significantly to the growth in Indonesia’s annual import volume. In turn, it has opened business opportunities for importers and distributors to enter into the soybeans market.Established as a family-owned business that trades physical soybeans in the West Java region, this paper intends to analyze and formulate a long-term strategy for PT. DKI as an example for the case study. In engaging with its business activities, the firm faces an array of internal and external challenges ranging from capacity constraints, size constraints and financial risks. The ultimate objective is to evaluate the prospects for diversifying related product portfolios and develop competing strategies while optimizing overall risk control and employing strategic partnerships ideas to streamline logistics processes in order to expand. Additional challenges the firm is facing in 2020 would be how the Coronavirus pandemic affected the livelihood of food-processing industries and end consumers, justifying a preemptive plan to adapt to the new business environment and shifting consumer demand. SWOT analysis is used as the primary methodology to assess the firm’s degree of competitiveness in the market and to develop the strategy matrix.To supplement the findings, trend analysis, ratio analysis, capacity analysis, risk analysis and marketsegmentation were utilized to identify bottleneck issues and assess the overall value of the firm. Theselected business and functional strategies integrate an improved business model; with the aim to overcome bottlenecks and optimize value transformation.Keywords: Soybeans, Commodities Import, Business Strategy